The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1186/1477-7517-7-25
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of HIV, hepatitis b, and hepatitis c among opioid drug users on methadone treatment in the netherlands

Abstract: BackgroundInjecting drug users (IDU) remain an important population at risk for blood-borne infections such as human immunodeficiency virus (HIV), hepatitis B virus (HBV) and hepatitis C virus (HCV). In the Netherlands, a program is being implemented to offer annual voluntary screening for these infections to opioid drug users (ODUs) screened in methadone care. At two care sites where the program is now operating, our study aimed to estimate the seroprevalence among ODUs screened for HIV, HBV and HCV; to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…The findings highlighted that a significant proportion of drug users had not received HBV screening. 20 Another study conducted in Switzerland found that nearly all methadone recipients had been tested for HIV (99%) or HCV (91%) 21 Several studies in India and Thailand have explored HIV and HCV uptake and its associated factors among IDUs recruited through peer-referral and targeted outreach. 22,23 These studies are focused on a single screening that may have overlooked the importance of co-infections.…”
Section: Introductionmentioning
confidence: 99%
“…The findings highlighted that a significant proportion of drug users had not received HBV screening. 20 Another study conducted in Switzerland found that nearly all methadone recipients had been tested for HIV (99%) or HCV (91%) 21 Several studies in India and Thailand have explored HIV and HCV uptake and its associated factors among IDUs recruited through peer-referral and targeted outreach. 22,23 These studies are focused on a single screening that may have overlooked the importance of co-infections.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, some categories in which the median proportion tested was 100% also included studies that reported relatively low levels of testing. For example, 33.6% of study participants in a study of people who use drugs were tested for HBV (39), and 13.0% of study participants in a study of asymptomatic patients in genitourinary medicine clinics were tested for HCV (59). However, we believe that our review findings around testing uptake are of limited value in assessing testing uptake levels in these populations because few studies had the specific purpose of examining HBV and HCV testing uptake.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has been linked to ongoing "at-risk" practices and has to be taken as an indication of the attitudes of non-compliance with preventive measures [54]. As with HIV, there is already considerations of a screening of HCV in adults [55] and IDU [56].…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%